2018
DOI: 10.1080/00071005.2018.1502872
|View full text |Cite
|
Sign up to set email alerts
|

Social scientists under threat: Resistance and self-censorship in Turkish academia

Abstract: Attacks on academic freedom in Turkey have become increasingly systematic in recent years and thousands of academics have been dismissed. This study reflects on the effects of this worsening repression through interviews with academics in the social sciences, both those dismissed and those still active in their profession. Although the dismissed academics are socially in a very precarious position, they are continuing their scholarly activities in alternative, underground forms. This resistance stands in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In countries such as Turkey [see, e.g. Özkirimli, 2017, p. 853;Scholars at Risk, 2017;Scholars at Risk, 2018;Aktas, Nilsson and Borell, 2019] and Hungary [e.g. Ignatieff, 2018;Scholars at Risk, 2018], the limitations imposed by authoritarian populist governments on freedom of the press and freedom of expression go hand in hand with restrictions to academic freedom.…”
Section: Authoritarian Populism and The Critique Against 'Liberal Academic Elite'mentioning
confidence: 99%
“…In countries such as Turkey [see, e.g. Özkirimli, 2017, p. 853;Scholars at Risk, 2017;Scholars at Risk, 2018;Aktas, Nilsson and Borell, 2019] and Hungary [e.g. Ignatieff, 2018;Scholars at Risk, 2018], the limitations imposed by authoritarian populist governments on freedom of the press and freedom of expression go hand in hand with restrictions to academic freedom.…”
Section: Authoritarian Populism and The Critique Against 'Liberal Academic Elite'mentioning
confidence: 99%
“…The academic dismissed with KHK is unable to work, travel, or access social security and health care for themselves or their families. “Dismissed with KHK” (by decree) as documented by Aktaş Nilsson, and Borell (2018), included cancelation of passports and the inability to work legally as even private employers will not hire someone with KHK on their record. As one respondent to a survey I carried out in spring 2019 described the experience,
When you are dismissed with a KHK, you are excluded by the society, left alone, all your friends around you disappear, you become unemployed and penniless, it is as if you are destined to death.
…”
Section: A Segue On Academic Freedommentioning
confidence: 99%
“…In an attempt to better understand the dynamics of identity for scholars in Turkey, and following work by Abbas and Zalta (2017) and Aktaş et al (2018), I developed a survey to be distributed to academics in Turkey whether employed or dismissed. Abbas and Zalta surveyed 60 respondents online, all of whom were Peace Academics.…”
Section: A Segue On Academic Freedommentioning
confidence: 99%
“…In previous study we interviewed 13 dismissed Turkish social scientists all of whom had signed the peace petitiontermed 'peace academics'as well as 15 other social scientists living in fear of being dismissed (Aktas et al, 2019). We found that scholars like these are often caught in a social impasse.…”
Section: Introductionmentioning
confidence: 97%
“…An interesting and paradoxical observation in our earlier interview study with dismissed researchers still active in their profession, was the stark contrast between the two groups. While the mood among researchers living with the threat of dismissal was summarised as 'a pervasive sense of resignation and lack of motivation', the social exclusion of dismissed researchers was rather 'a defiant sense of newly found freedom, of no longer needing to avoid sensitive issues' (Aktas et al, 2019). That is, despite their efforts the regime did not manage to silence discharged scholars.…”
Section: Introductionmentioning
confidence: 99%